Core outcome sets in women's and newborn health: a systematic review. (21st August 2017) - Duffy, JMN; Rolph, R; Gale, C; Hirsch, M; Khan, KS; Ziebland, S; McManus, RJ; ,
Abstract : Background: Variation in outcome collection and reporting is a serious hindrance to progress in our specialty; therefore, over 80 journals have come together to support the development, dissemination, and implementation of core outcome sets. Objective: This study systematically reviewed and characterised registered, progressing, or completed core outcome sets relevant to women's and newborn health. Search strategy: Systematic search using the Core Outcome Measures in Effectiveness Trial initiative and the Core Outcomes in Women's and Newborn Health initiative databases. Selection criteria: Registry entries, protocols, systematic reviews, and core outcome sets. Data collection and analysis: Descriptive statistics to describe characteristics and results. Results: There were 49 core outcome sets registered in maternal and newborn health, with the majority registered in 2015 ( n = 22; 48%) or 2016 ( n = 16; 32%). Benign gynaecology ( n = 8; 16%) and newborn health ( n = 3; 6%) are currently under‐represented. Twenty‐four (52%) core outcome sets were funded by international ( n = 1; <1%), national ( n = 18; 38%), and regional ( n = 4; 8%) bodies. Seven protocols were published. Twenty systematic reviews have characterised the inconsistency in outcome reporting across a broad range of relevant healthcare conditions. Four core outcome sets were completed: reconstructive breast surgery (11 outcomes), preterm birth (13 outcomes), epilepsy in pregnancy (29 outcomes), and maternity care (48 outcomes). The quantitative, qualitative, and consensus methods used to develop core outcome sets varied considerably. Conclusions: Core outcome sets are currently being developed across women's and newborn health, although coverage of topics is variable. Development of further infrastructure to develop, disseminate, and implement core outcome sets is urgently required. Tweetable abstract: Forty‐nine women's and newborn core outcome sets registered. 50% funded. 7 protocols, 20 systematic reviews, and 4 core outcome sets published. @coreoutcomes @jamesmnduffy Tweetable abstract: Forty‐six women's and newborn core outcome sets registered. 50% funded. 7 protocols, 20 systematic reviews, and four core outcome sets published. @coreoutcomes This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14694 .